Ohranjanje biotske raznovrstnosti v slovenskem kmetijstvu v luči mednarodne pravne ureditve - Žigo Jonozovič, Aleksandra (visokošolska dela, 2004)
This thesis deals with the issues associated with the protection of the agricultural biodiversity in Slovenia, with an emphasis on the legal regulations in this area. After analyzing the legal sources, stratigic programs and other pertinent documents, we have determined the deviations in Slovenia from European and international norms of conservation and its associated activities. The state of affairs in Slovenia is examined within theframework of the European Union and activities taking place on the international level. The concept of intellectual property rights over agricultural genetic resources is also examined. Slovenian legislation concerning the protection of agricultural biodiversity suffers from both a lack of defined terminology and deficiencies in the terminology that does exist. In Slovenia, there is no connection between environmental and agricultural legislation regarding agricultural genetic resources; there is nosatisfactory resolution to outstanding issues in the area of intellectual property and in the area of access to agricultural genetic resources; and there is no harmonized development of regulations in the area of conservation of the genetic resources of plants and animals in agriculture. There is also no national body to coordinate work in this area. In this paper we have analyzed the concept of autochthonous agricultural genetic material and proposed a scheme for defining it. We have also proposed a possible way of inserting aspects of biodiversity into the environmental legislation by assigning the status of "natural value" to those aspects of agricultural genetic diversity which have a particular historical, cultural, and scientificvalue for Slovenia. Slovenia needs legislation that will completely cover the area of conservation of agricultural biodiversity and become a firm basis on which further development in this area can take place.
Keywords: agriculture; Kmetijstvo; biodiversity; Biološka raznovrstnost; Magistrske naloge; Genski viri; Zaščita; Zakonodaja; Slovenia; Slovenija; intelektualna lastnina; naravne vrednote